Teaching and learning : the essential readings - Desforges, Charles; Fox, Richard, 1945-; Wiley InterScience (Online service) (Oxford ; Malden, MA : Blackwell, 2002)
This is the first collection of key articles on the psychology behind educational attainment. It brings together in one volume for students a set of accessible but influential papers, representing the best classic and cutting edge work in the field. Under the themes of basic processes in learning, interactions between teachers and learners, and metacognitive approaches to learning, the thirteen readings cover a wide range of topics. To help students gain an overview of the subject, each article is introduced and contextualized by the editors, as is the volume as a whole. Each paper is also accompanied by suggestions for further reading so that students can investigate topics in more depth if they wish. This book of readings can be used alone or alongside a text on teaching and learning. In either context, it offers an ideal starting point for the exploration of key issues in educational attainment.
Attaining excellence through deliberate practice: insights from the study of expert performance / K. Anders Ericsson -- Rhyme, language, and children's reading / Peter Bryant, Morag MacLean, and Lynette Bradley -- The rebirth of children's learning / Robert S. Siegler -- Candy selling and math learning / Geoffrey B. Saxe -- Understanding academic performance at university: a research retrospective / Noel J. Entwistle -- On becoming a tutor: toward an ontogenetic model / David Wood [and others] -- Teacher expectations: implications for school improvement / Colin Rogers -- An exploration of long-term far-transfer effects following an extended intervention program in the high school science curriculum / Philip Adey and Michael Shayer -- Reconstructing context: the conventionalization of classroom knowledge / Derek Edwards and Neil Mercer -- The role of assessment in a learning culture / Lorrie A. Shepard.
Includes bibliographical references and index.
Print version record.
Keywords: Teaching -- Psychological aspects; Learning, Psychology of; Educational psychology; Enseignement -- Aspect psychologique; Apprentissage, Psychologie de l'; Psychopédagogie.; Educational psychology; Learning, Psychology of; Teaching -- Psychological aspects; Leren; Ontwikkeling (psychologie); Onderwijspsychologie; Electronic books; Electronic books; Electronic resource